Validating MEGUX: reliability and validity of a mobile educational game UX instrument - Syed Yasin, Sharifah Nurulhikmah; Ibrahim, Roslina (Universiti Teknologi MARA, Perak, 2025)
Mobile educational games (MEGs) blend gameplay and pedagogy on smartphones and tablets, yet existing UX frameworks focus on general usability, entertainment gaming, or desktop e‑learning and do not fully address the mobile context or the dual aims of learning and engagement. This study evaluates the MEGUX model internal consistency and known‑groups validity by comparing two programming‑learning games. Following an eight‑phase UX instrument development process, a set of an 88‑item pool across six dimensions (Flow, Immersion, Player Context, Game Usability, Mobility, Learning) was generated. After expert review and pilot testing, MEGUX was administered to 265 undergraduates (AlgoRun, n = 161; Rodocodo, n = 104) over a one‑week play period in March–April 2025. Internal consistency was assessed via Cronbach’s a and known‑groups validity was tested with independent‑samples t‑tests (with Levene’s checks) and Cohen’s d effect sizes. Cronbach’s a values ranged from .820 (Player Context) to .899 (Flow, Learning), indicating strong reliability. Rodocodo significantly outperformed AlgoRun on 70 of 88 items (p < .05,d = 0.23−0.74), demonstrating MEGUX’s sensitivity to UX differences in real‑world MEGs. MEGUX is a comprehensive and robust instrument for evaluating UX in mobile educational games, offering designers and researchers a reliable tool to identify strengths and weaknesses in engagement and learning components.